2016
DOI: 10.1016/j.jht.2015.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Robot training for hand motor recovery in subacute stroke patients: A randomized controlled trial

Abstract: Robotic therapies may be useful during the subacute stages of stroke - both endpoints (FM hand and MI prehension) showed the expected trend with bigger effect size for the robotic intervention. Additional benefit of the robotic therapy over the control therapy was only significant when the difference was measured with FM, demanding further investigation with larger samples. Implications of this study are important for decision making during therapy administration and resource allocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
9

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 44 publications
2
76
0
9
Order By: Relevance
“…In fact, these devices allow to increase of the amount and intensity of the therapy, to standardize the treatment, providing a complex but controlled multisensory stimulation [9,10] and helping the patient to complete the required task while preventing inappropriate movements [11]. Even if most of the robots focuses on the more proximal joints (shoulder and elbow) [12], some devices have been specifically developed to target the hand, using either end-effector [13][14][15] or exoskeleton [16,17] design, with encouraging results in terms of motor recovery [12,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, these devices allow to increase of the amount and intensity of the therapy, to standardize the treatment, providing a complex but controlled multisensory stimulation [9,10] and helping the patient to complete the required task while preventing inappropriate movements [11]. Even if most of the robots focuses on the more proximal joints (shoulder and elbow) [12], some devices have been specifically developed to target the hand, using either end-effector [13][14][15] or exoskeleton [16,17] design, with encouraging results in terms of motor recovery [12,[18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade alone, over 140 hand exoskeletons have been developed, 46 of which were declared as daily assistive devices [1]. In contrast to stationary rehabilitation devices [2], [3], wearable assistive tools are designed to be used and worn throughout the entire day and, therefore, are dramatically restricted in size and weight. In a study with 242 upper limb prosthesis users, low added weight to the arm was found to be the most important design factor [4] and in neurological patients added weight leads to faster fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…54 [2,3]. Similarly, other studies focusing solely on robot-assisted rehabilitation of hand function in chronic [48][49][50][51] or subacute stroke [12,52,53] were not able to show statistically significant differences between robot and control therapy groups, or reported minor differences in secondary outcome measures [10,54,55]. The present RCT directly investigated equivalence in motor impairment reduction between a robot-assisted and a conventional therapy group focusing on the training of the upper limb, and in particular the hand.…”
Section: Changes In Secondary Outcome Measuresmentioning
confidence: 73%